Feasibility of Mindfulness-Based Stress Reduction for older adolescents and young adults with poorly controlled type 1 diabetes. Issue 1 (1st January 2018) - Ellis, Deborah A.; Carcone, April; Slatcher, Richard; Sibinga, Erica
ABSTRACT: Objective: The purpose of the study was to assess the acceptability and feasibility of Mindfulness-Based Stress Reduction (MBSR), a group-delivered intervention, to reduce stress and improve illness management among urban, older adolescents, and young adults with poorly controlled type 1 diabetes (T1D). Method: Ten older adolescents and young adults (9 females, 1 male) were recruited to participate in an MBSR group. Acceptability and feasibility were assessed based on recruitment and retention, treatment satisfaction, and changes in stress, diabetes management, and health status using a mixed-methods approach. Results: Satisfaction with MBSR was high based on both quantitative and qualitative data. Preliminary evidence was found to suggest that MBSR reduced stress and improved blood glucose levels. Conclusions: Findings from a small feasibility study suggest that MBSR could be delivered to urban older adolescents and young adults with T1D with high rates of satisfaction. Additional testing in adequately powered controlled clinical trials appears warranted.